Poly(2-ethyl-2-oxazoline)–PLA-g–PEI amphiphilic triblock micelles for co-delivery of minicircle DNA and chemotherapeutics - Gaspar, Vítor Manuel Abreu (2018)
The design of nanocarriers for the delivery of drugs and nucleic-acids remains a very challenging goal due to their physicochemical differences. In addition, the reported accelerated clearance and immune response of pegylated nanomedicines highlight the necessity to develop carriers using new materials. Herein, we describe the synthesis of amphiphilic triblock poly(2-ethyl-2-oxazoline)–PLA-g–PEI (PEOz–PLA-g–PEI) micelles for the delivery of minicircle DNA (mcDNA) vectors. In this copolymer the generally used PEG moieties are replaced by the biocompatible PEOz polymer backbone that assembles the hydrophilic shell. The obtained results show that amphiphilic micelles have low critical micellar concentration, are hemocompatible and exhibit stability upon incubation in serum. The uptake in MCF-7 cells was efficient and the nanocarriers achieved 2.7 fold higher expression than control particles. Moreover, mcDNA-loaded micelleplexes penetrated into 3D multicellular spheroids and promoted widespread gene expression. Additionally, to prove the concept of co-delivery, mcDNA and doxorubicin (Dox) were simultaneously encapsulated in PEOz–PLA-g–PEI carriers, with high efficiency. Dox–mcDNA micelleplexes exhibited extensive cellular uptake and demonstrated anti-tumoral activity. These findings led us to conclude that this system has a potential not only for the delivery of novel mcDNA vectors, but also for the co-delivery of drug–mcDNA combinations without PEG functionalization.